Jet-evolution in the quark-gluon plasma from RHIC to the LHC - Domdey, Svend Oliver; Kopeliovich, Boris Z.; Pirner, Hans J. (Nuclear physics. A, Nuclear and hadronic physics, 2011)
The observed suppression of high-p⊥ hadrons allows different explanations. We discuss two possible scenarios: In scenario 1, parton energy loss from scattering in the hot medium is complemented by final state interactions in the resonance matter. Scenario 2 has an enhanced transport parameter qˆ which is fitted to RHIC data. For LHC, the two scenarios lead to very different predictions for the nuclear modification factor of hadrons. In addition, jet reconstruction allows more specific tests of the mechanisms responsible for jet quenching. We calculate the distribution of partons inside a jet and find different results for the two scenarios.
Available online 3 March 2011
Gesehen am 20.06.2022